Mexico : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This report assesses the Observance of Standards and Codes on the Financial Action Task Force (FATF) Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for Mexico. The report highlights that Mexico has removed specific exemptions to customer identification obligations, implemented online reporting forms and a new automated transmission process for reporting transactions to the financial intelligence unit. Financial institutions with a reporting obligation (reporting institutions) now require occasional customers performing transactions equivalent to or exceeding USD 3,000 in value to be identified so that the transactions can be aggregated daily.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet